Creatine supplementation in the elderly: Main implications and benefits (Research, Society and Development, 2024)
Human aging is characterized by gradual and progressive decrease in functional and cognitive capabilities. Faced with this scenario, there is an urgent need for strategies aimed at improving the quality of life of this population. Faced with complications associated with the loss of muscle mass and cognitive function, this article's main objective was to raise the main scientific findings related to the applicability, benefits implications of creatine supplementation in the elderly, especially in maintaining muscle mass and cognitive function. The integrative review was carried out based on scientific articles selected from the Public Medline (PubMed) and Scholar Google, published between 2018 and 2024, in Portuguese and English. Creatine supplementation can preserve muscle mass and cognitive function, especially when combined with resistance exercise. However, the response to supplementation varies depending on the individual profile, such as the presence of chronic diseases and the use of medications. However, although creatine supplementation combined with personalized interventions has potential in maintaining muscle mass and cognitive function, a greater number of studies should be conducted considering the complexity of aging and the different demands.